Cobalt(iii) catalyzed C-8 selective C–H and C–O coupling of quinoline N-oxide with internal alkynes via C–H activation and oxygen atom transfer. Issue 7 (23rd December 2015) - Barsu, Nagaraju; Sen, Malay; Premkumar, J. Richard; Sundararaju, Basker
Abstract : An efficient, scalable, atom-economical, regio-selective air stable Cp*Co(iii ) catalyzed C–H and C–O coupling via a C–H activation/oxygen atom transfer reaction of quinoline N -oxide and an internal alkyne is reported. Abstract : An efficient, scalable, atom-economical, regio-selective air stable Cp*Co(iii ) catalyzed C–H and C–O coupling via a C–H activation/oxygen atom transfer reaction of quinoline N -oxide and an internal alkyne is reported. Such a catalytic transformation is witnessed for the first time with a cobalt catalyst and using N -oxide as a traceless directing group, in contrast to the existing literature. The developed synthetic methodology is straightforward and possesses various functional group tolerances, including heterocycles.